2006
DOI: 10.1080/16501970500476142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Quality of Life, Exercise Capacity and Pulmonary Function in Children With Asthma

Abstract: Eight weeks of regular submaximal exercise has beneficial effects on quality of life and exercise capacity in children with asthma. Submaximal basketball training is an effective alternative exercise program for asthmatic children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
136
3
19

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(171 citation statements)
references
References 29 publications
13
136
3
19
Order By: Relevance
“…Failure to achieve a significant difference between groups could be due to the inclusion of subjects that are already wellcontrolled, leaving little room for improvement, and to a type II error due to small sample size. This is in contrast with the trial of BASARAN et al [34], in which a significant improvement occurred in the exercise group compared to control group. However, in that study, a significant baseline difference in symptom scores was observed between groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Failure to achieve a significant difference between groups could be due to the inclusion of subjects that are already wellcontrolled, leaving little room for improvement, and to a type II error due to small sample size. This is in contrast with the trial of BASARAN et al [34], in which a significant improvement occurred in the exercise group compared to control group. However, in that study, a significant baseline difference in symptom scores was observed between groups.…”
Section: Discussioncontrasting
confidence: 55%
“…Because asthma is the most prevalent chronic disease in children and adolescents, because most asthma patients have mild intermittent or mild persistent disease, (1) and because regular physical activity has been proven to have beneficial effects, (7)(8)(9) it is essential to determine whether asthma has negative effects on exercise capacity between attacks, the approach to physical training being based on the answer to this question. Therefore, the objective of the present study was to assess children and adolescents with mild intermittent or mild persistent asthma, in terms of their aerobic capacity between attacks.…”
Section: Introductionmentioning
confidence: 99%
“…18 Although the level of evidence is not high for several of the non-pharmacologic therapies, most have little or no adverse effects. 26,27 Therefore, non-pharmacologic treatment for EIB is an area with many questions for continued research. 18,19 In fact, to our knowledge, no study has evaluated the obesityrelated inflammatory biomarkers and their influence on EIB in obese adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…Despite many studies being conducted to date, there is no single agent that has been consistently shown to prevent EIB; moreover, the majority of the studies were with asthmatic patients. [25][26][27] The goal of therapy is to allow patients with EIB to participate in vigorous activity without symptoms and difficulty. 18 Although the level of evidence is not high for several of the non-pharmacologic therapies, most have little or no adverse effects.…”
Section: Introductionmentioning
confidence: 99%